La preghiera ebraica femminile (Altre Modernità, 2014)
The prayers made by women in Hebrew Literature represent a wide field of research and open many complex questions. On the one hand, Hannah's prayer, Myriam and Deborah's songs show that feminine expressions, with some themes and a style of their own, exist since the Bible. Also in the Medieval and Renaissance periods we have evidence of many Jewish women's prayers,but we usually deal with oral traditions. Sometimes the extant texts came to us because they were written down on manuscripts as addenda to ancient prayers (like the tefillà yafà); alternatively, they were transmitted orally till the modernity (Sefardic songs).For that reason, another method to individuate them is to examine external sources, such as the Inquisition documents. Only rarely, and in more recent periods, we deal with texts of prayers which were consciously composed by women (like Glickel von Hameln). At the contrary, with the Modern Age, since the presence of Jewish women in Hebrew Literature is strong, many examples of 'feminine' prayers are recorded, till the Israeli Literature, with authors like Zelda or Esther Raab. After dealing with a general view on texts composed by women from the Bible to the Contemporary Literature, this article asks how to individuate the feminine inspiration in the hebrew texts of prayers. One method would be to examine manuscripts copied by women; also the oral traditions and the external sources need to be deeply analyzed: doing so, we would be able to find the themes of women literary production and enrich our knowledge with new discoveries.
Keywords: donne ebree; preghiera al femminile; Bibbia; manoscritti ebraici di donne